Pengaruh Kemudahan Menggunakan Teknologi Dan Manfaat Menggunakan Teknologi Terhadap Kepercayaan (Studi Kasus Pada Konsumen Ritel) - Laura Lahindah; Ronny Samsul Bahri (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2022)
The development of the retail business is very important in supporting Indonesia's economic growth.Â In the context of changing shopping behavior patterns since the COVID-19 pandemic, Information and Communication Technology plays an important role. In the transformation process from offline shopping behavior patterns to online, trust becomes one of the important variables in the process. Trust can be defined as a specific set of beliefs related to the integrity, benevolence, and abilities of the other party. Trust is influenced by several variables including the ease of use of ICT and the benefits of using ICT which ultimately makes consumers believe in the retailer's ability to meet their needs. This study aims to determine whether there is an influence between the ease of using ICT on trust and the benefits of using ICT on trust. The survey was conducted on 41 retail consumers who have experienced shopping on online and offline channels. The results show that there is an influence between the ease of using ICT on trust, and there is influence between the benefits of using ICT on trustÂ Keywords: Trust, Perceive Ease Of Used, Perceive Ease Of Usefulness, Retail